2005
DOI: 10.1248/bpb.28.1986
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Diabetes Model in Chick Embryos Treated with Streptozotocin

Abstract: The aim of the present study was to investigate whether diabetes model can be made by treatment of streptozotocin (STZ) in chick embryos and this model can be used to predict the effect of drug. When STZ (0.3 mg/egg) was injected into the albumen of fertile eggs on the 14th day of incubation, level of blood glucose significantly increased than that of the control on the 17th day of incubation, and level of serum insulin significantly decreased. In addition, the enhanced level of blood glucose in STZ-treated em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 12 publications
0
28
0
1
Order By: Relevance
“…In contrast to the rat, adult chicks have been reported to be resistant to streptozotocin-induction of diabetes (Simon and Dubois, 1980; Stellenwerf and Hazelwood, 1979). However, chick embryos appear amenable to streptozotocin diabetes induction (Shi et al, 2014; Yoshiyama et al, 2005). Yoshiyama et al (2005) injected streptozotocin into the albumen of fertilized eggs day 14 of incubation and showed decreased insulin and elevated glucose levels at day 17.…”
Section: Current Research Applications: Chick Models For Human Dismentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the rat, adult chicks have been reported to be resistant to streptozotocin-induction of diabetes (Simon and Dubois, 1980; Stellenwerf and Hazelwood, 1979). However, chick embryos appear amenable to streptozotocin diabetes induction (Shi et al, 2014; Yoshiyama et al, 2005). Yoshiyama et al (2005) injected streptozotocin into the albumen of fertilized eggs day 14 of incubation and showed decreased insulin and elevated glucose levels at day 17.…”
Section: Current Research Applications: Chick Models For Human Dismentioning
confidence: 99%
“…However, chick embryos appear amenable to streptozotocin diabetes induction (Shi et al, 2014; Yoshiyama et al, 2005). Yoshiyama et al (2005) injected streptozotocin into the albumen of fertilized eggs day 14 of incubation and showed decreased insulin and elevated glucose levels at day 17. Shi et al (2014) then demonstrated that injection of streptozotocin in the amniotic layer at embryonic day 12 produced typical ocular sequelae of diabetes, including cataract, retinal thinning, ERG abnormalities, and insulin-related signaling changes that were similar to those reported in the streptozotocin rat model.…”
Section: Current Research Applications: Chick Models For Human Dismentioning
confidence: 99%
“…Malformations associated with diabetic pregnancy affect many major organ systems, such as the central nervous, cardiovascular, gastrointestinal, urogenital, and musculoskeletal systems [83]. The infant of the diabetic mother has an increased risk for several neonatal complications, such as macrosomia, hypoglycemia, hypocalcemia, polycythemia, and hyperbilirubinemia.…”
Section: Chick Embryo As a Model For Depicting Glucose-induced Malformentioning
confidence: 99%
“…Angiogenesis diperlukan dalam proses pertumbuhan embrio, maupun proses-proses perbaikan fisiologis saat postnatal. Proses vaskulo-angiogenesis pada embrio sering dipelajari dengan menggunakan embrio ayam (maupun famili aves lainnya) karena lebih mudah dipelajari [3,8], serta untuk mengurangi penggunaan mamalia sebagai hewan coba [9]. Angiogenesis yang berjalan abnormal mengakibatkan berbagai proses patologis.…”
unclassified